Analisis Manajemen Sumber Daya Insani pada BAZNAS Kota Metro - Khusnul Mualimin; Nafian Dafa Fahrezi; Lilis Renfiana (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Human resources are people who work in an organization's environment who are usually called employees, staff, personnel. This study examines how human resources play a crucial role in the smooth operations of Baznas institutions, which are the entities responsible for managing zakat. With the aim of seeing how far the principles of human resource management are applied at the institution. The method used in this research is field research with a descriptive approach. The data sources used in this research are primary and secondary data sources, where primary data was obtained from direct interviews with Baznas leaders in metro cities, while secondary data was obtained from journals and books. The results of the research show that the metro city Baznas has implemented human resource management well in accordance with legal and sharia provisions, such as selection, recruitment, assessment and training, the selection and recruitment carried out by the metro city Baznas has met the requirements set by the agency. center, so that things like intimidation and fraud do not occur. Furthermore, the assessment and training process for metro city Baznas staff is quite good, because in this process the supervisors carry out the training and assessment so they can see the extent of employee performance and find out how much potential and responsibility the human resources at city Baznas have metro.